2001
DOI: 10.1080/00039890109604057
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Blood Levels of Pentachlorophenol (PCP) with Cellular and Humoral Immunodeficiencies

Abstract: It has long been suspected that pentachlorophenol (PCP) exerts a damaging influence on the immune system. In this study, the possible relationship between blood levels of PCP and immune function was studied in 190 patients who had been exposed for more than 6 mo to PCP-containing pesticides. The patients suffered from frequent respiratory infections and general fatigue. Lymphocyte subpopulations, in-vitro responses to mitogens, allogeneic stimulator cells, plasma neopterin, cytokines, soluble cytokine receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…The weak associations of PCBs, HCB, and HCHs with immunologic abnormalities described herein are in stark contrast to the striking abnormalities observed in individuals with high blood levels of PCP (38,49). The clinical relevance of HCB-associated suppression of IFN-γ awaits further clarification.…”
Section: Nscontrasting
confidence: 49%
See 2 more Smart Citations
“…The weak associations of PCBs, HCB, and HCHs with immunologic abnormalities described herein are in stark contrast to the striking abnormalities observed in individuals with high blood levels of PCP (38,49). The clinical relevance of HCB-associated suppression of IFN-γ awaits further clarification.…”
Section: Nscontrasting
confidence: 49%
“…Because PCP was shown in previous studies to be strongly associated with humoral and cellular dysfunction, we excluded individuals with PCP blood levels > 10 µg/L from the analysis (38,49). The blood levels of PCBs, HCB, and HCHs were often associated with one another, suggesting simultaneous exposure, making it difficult to dissociate the impact of individual compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agent Orange, an herbicide used in Vietnam War was also found to be toxic to immune function (Kim et al, 2003). Pentachlorophenol, -cies, which is associated with the increased blood levels of Pentachlorophenol (Daniel et al, 2001). 3,4-dichloropropionaniline is also a herbicide, and suppresses several to suppresses normal macrophage function (Ustyugova et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Stiller-Winkler et al (1999) reported that the exposure of humans to a mixture of pesticides such as organophosphates, carbamates, phenoxy herbicides and pyrethroids resulted in a significant increase in serum neopterin in comparison to a non-exposed group. Blood concentrations of pentachlorophenol also correlated positively with plasma concentrations of neopterin (Daniel et al 2001a). In contrast, serum neopterin gave no indication of significant changes after pesticide control operation using pyrethroids (Hadnagy et al 2003) and plasma neopterin showed no associations with blood concentrations of polychlorinated biphenyls, hexachlorocyclohexane isomers and hexachlorobenzene (Daniel et al 2001b).…”
Section: Discussionmentioning
confidence: 92%